A responsabilidade civil objetiva genérica fundada na atividade de risco: (teoria geral e hipóteses práticas) - Souza, Wendell Lopes Barbosa de (2009)
Where the fee is there should be the load. Who gains the bonus should support the load. Finding the deficiency in the theory subjected to verification that the necessity from the demonstration of guilt affected by the harmful agent of the law would leave the victim with no reimbursement in most cases. The appearance of the objective theory resulted from applying the risk doctrine. Emergence of various legal norms have input the duty of indemnification for determine concrete situations, dealing with the foreseen or closed objective civil responsibility. Opening of this reimbursement system, expecting that the precarious activity for the right of others; triggers for the criminal an obligation to repair the damage without the questioning of his culpability, dealing with the generic objective civilian responsibility second part of the only paragraph in article 927 of the Brazilian Civil Code, Typical hypothesis of the generic objective responsibility theory through risk activity, such as the manufacturing, the stocking, the handling, and the transportation of flammable and explosive substances. Hypothesis for the questioning, such as driving, bank activities, the credit card, the electronic commerce, the protection and transport of valuables, the security and escort services, the civil construction, the entries of credit protection, the capital market, the loan of vehicles to third parties, the cigarette fabrication and distribution, the employer s responsibility with employee s accidents, the communication businesses, the nuclear and radioactive installations, sports practices and other activities that could give opportunity to the generic objective responsibility based on the risk activity. Situations that may or may not distance indemnification duty in this type of civil responsibility, such as the necessity state, the self-defense, the daily practice of a right, sudden cases or unpredictable events, a third person involvement, the exclusive guilt of the victim, the precautions taken to avoid the accident and the legal activity of the harmful agent